How Global is the Global Internet? First Steps Towards a Policy-Economic Analysis - Morganti, Luciano (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2007)
Who exactly are the main players behind the technical infrastructure of the Internet? What paths are emerging at a global level about the use of the Internet? Where and by whom is content produced and consumed? To put it more colloquially, who are the ‘spiders’ of the Internet and how are they actually spinning their webs. These aspects, together with the issue of Internet governance, are amongst the most critical and important elements to understand how the Internet’s political economy is articulating itself. In order to start an analysis of the Internet’s political economy, this article concentrates on the first two aspects: a technical analysis, which aims at understanding who is behind the Internet infrastructure, client and server applications, and paths of content production and consumption; and an assessment of which cultures and regions in the world are developing into important Internet players. The two parts are complemented by a critical assessment that aims to clarify why these issues are important in order to establish a first sketch of the Internet political economy. This article presents a multi-level and multi-disciplinary analysis to technology development, very much in line with a socioconstructivist approach, in which technology and infrastructure, players and interests, and models of societal appropriation are considered as equally important. It will hopefully generate a first idea of how to map the main types of shareholders directly and indirectly interested and involved in the issue of Internet governance and what are the most important points of attention for scholars interested in the topic of Internet political economy. This will lead to the formulation of a number of research questions, shaping and building a more articulated and coherent approach into research about the political economy of the Internet.